Ln (x ^ 2-x) -ln (5x) = -3 ise x nedir?

Ln (x ^ 2-x) -ln (5x) = -3 ise x nedir?
Anonim

Cevap:

#, X = 1 + 5e ^ (- 3) #

Açıklama:

#ln (x ^ 2-x) -ln (5x) = - 3 #

Unutmayın ki logaritmaları yalnızca pozitif sayılara uygulayabiliriz:

Yani # x ^ 2-x> 0 ve 5x> 0 #

#x (x-1)> 0 ve x> 0 => x> 1 #

Şimdi denklemi çözelim:

#ln (x ^ 2-x) = - 3 + ln (5x) #

#color (kırmızı) (a = ln (e ^ a) #

#ln (x ^ 2-x) = İn (e ^ (- 3)) + ln (5x) #

#color (kırmızı) (ln (a) + ln (b) = ln (a * b) #

#ln (x ^ 2-x) = İn (5e ^ (- 3) x) #

#color (kırmızı) (ln (a) = ln (b) => a = b #

# X, ^ 2-x = 5e ^ (- 3) x #

# X ^ 2- 5e ^ (- 3) 1, x = 0 #

# {X- 5e ^ (- 3) 1} x = 0 #

#cancel (x = 0) #(dominiumda değil) veya #, X = 1 + 5e ^ (- 3) #